Optimizing water–nitrogen coupling for quinoa yield, quality, and resource use efficiency in arid regions - Li, Xinyue; Shen, Zhaotong; A, Yingge; Zhao, Yupeng; Yang, Bin; Feng, Yaozu; Bian, Qingyong; Fu, Yanbo (Frontiers in Plant Science, 2025)
IntroductionTo investigate the effects of water–nitrogen coupling under drip irrigation on quinoa yield, quality, and water–nitrogen use efficiency, a microplot experiment was conducted in Aksu Prefecture, Xinjiang.MethodsThe study employed a two-factor factorial design with three irrigation levels (W1: 2,100 m3/ha, W2: 2,700 m3/ha, W3: 3,300 m3/ha) and five nitrogen application rates (N0: 0 kg/ha, N1: 100 kg/ha, N2: 125 kg/ha, N3: 150 kg/ha, N4: 175 kg/ha), resulting in 15 treatment combinations. Results and discussionResults indicated that under the W1 irrigation level, increasing nitrogen application enhanced dry matter accumulation. However, under W2 and W3 conditions, dry matter declined when nitrogen exceeded 150 kg/ha, indicating a significant nitrogen threshold effect. A yield response model (R² = 0.945) predicted a maximum theoretical yield of 4,363.91 kg/ha at an irrigation volume of 2,931.59 m3/ha and a nitrogen application rate of 149.24 kg/ha. Optimal grain quality—characterized by fat content of 51.47–55.90 g/kg, protein content of 189.68–199.05 g/kg, and starch content of 581.23–585.96 g/kg—was observed under W2 and W3 combined with N2 and N3 treatments. Regression analyses indicated peak values for water use efficiency (WUE), nitrogen agronomic efficiency (NAE), and nitrogen partial factor productivity (NPFP) at 1.64, 29.72, and 31.92 kg/kg, respectively. Based on these findings, a recommended water–nitrogen management strategy for quinoa production in southern Xinjiang is 2,700 m3/ha of drip irrigation water combined with 150 kg/ha of nitrogen fertilizer, achieving a balance among high yield, resource efficiency, and environmental sustainability.